PENGARUH PENERAPAN PENDEKATAN SAVI BERBANTUAN LKS TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII MTSN KEPALA HILALANG PADANG PARIAMAN - Ismiyati Ismiyati (Universitas Negeri Padang, 2014)
The article based on research that title “Influence of using SAVI approach assisted student worksheet to the ability of the students in grade VIII of MTsN Kepala Hialang Padang Pariaman”. This research based of fact in the school that teaching and learning process was teacher centered. The students just relied teacher lesson explanation so that the student be passive in learning process. The purpose of this research to detection influence of using SAVI approach assisted student worksheet to the ability of the students in grade VIII MTsN Kepala Hilalang Padang Pariaman. The research of type is quasi-exsperiment research and design is randomized control group only design. The population of the research was grade VIII in MTsN Kepala Hialang and sample was selected by applying cluster random sampling technique. The research of data was learning outcome is three aspect. They were cognitive, affective and psikomotor. The data was analyzed by hypothesis test about equality test of two averages which use t test. The conclude of this research that there influence of used SAVI approach assisted student worksheet give significance to learning outcome of grade VIII MTsN Kepala Hilalang for cognitive, affective, and psikomotor aspect at significance level 5%